The role of serotonin 5-HT2A receptors in memory and cognition - Zhang, Gongliang; Stackman, Robert W. (Frontiers in Pharmacology, 2015)
Serotonin 5-HT2A receptors (5-HT2ARs) are widely distributed in the central nervous system, especially in brain region essential for learning and cognition. In addition to endogenous 5-HT, several hallucinogens, antipsychotics, and antidepressants function by targeting 5-HT2ARs. Preclinical studies show that 5-HT2AR antagonists have antipsychotic and antidepressant properties, whereas agonist ligands possess cognition-enhancing and hallucinogenic properties. Abnormal 5-HT2AR activity is associated with a number of psychiatric disorders and conditions, including depression, schizophrenia, and drug addiction. In addition to its traditional activity as a G protein-coupled receptor, recent studies have defined novel operations of 5-HT2ARs. Here we review progress in the 1) receptor anatomy and biology: distribution, signaling, polymerization and allosteric modulation; and 2) receptor functions: learning and memory, hallucination and spatial cognition, and mental disorders. Based on the recent progress in basic research on the 5-HT2AR, it appears that post-training 5-HT2AR activation enhances nonspatial memory consolidation, while pre-training 5-HT2AR activation facilitates fear extinction. Further, the potential influence that 5-HT2AR-elicited visual hallucinations may have on visual cue (i.e., landmark) guided spatial cognition is discussed. We conclude that the development of selective 5-HT2AR modulators to target distinct signaling pathways and neural circuits represents a new possibility for treating emotional, neuropsychiatric and neurodegenerative disorders.